LANGUAGE STYLE IN SUNTORY GARUDA BEVERAGE PRODUCTS ON THE OFFICIAL WEBSITE - Kristian, Michael Rovendo; Nirwan, Nirwan; Mujani, Sahril (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study looks at the language used on Suntory Garuda's official website in their beverage product advertisements. The choice of language used in advertising is crucial since it can significantly affect how buyers view the product and how well it speaks to them. The study focuses on the use of figurative language, such as personification, similes, and metaphors, in order to fully comprehend stylistics. These techniques rely on deeper meanings and imagery that go beyond literal interpretations of words. The study also examines how advertising helps consumers become more aware of their options, build trust, and satisfy their desires. the grown of social media, has prompted an evolution in advertising to reach a large audience quickly and interactively. Sensible and thoughtful wording arouses emotions, crafts messages that stick in your memory, and establishes a powerful brand identity. This type of wording has the power to elevate or detract from an advertisement. The primary objective of this study is to comprehend Suntory Garuda's language style and how it influences the brand's reputation and customer involvement. The findings of this study have the potential to improve understanding of how language is effectively used in advertisements and how it affects consumer attitudes and decisions.